Relationship between Personal Ethics and Burnout: The Unexpected Influence of Affective Commitment - Carlos Santiago-Torner; José-Antonio Corral-Marfil; Elisenda Tarrats-Pons (Administrative Sciences, 2024)
Objective: Ethical climates and their influence on emotional health have been the subject of intense debates. However, Personal Ethics as a potential resource that can mitigate Burnout syndrome has gone unnoticed. Therefore, the main objective of this study is to examine the effect of Personal Ethics on the three dimensions that constitute Burnout, considering the moderating influence of Affective Commitment. Design/methodology: A model consisting of three simple moderations is used to solve this question. The sample includes 448 professionals from the Colombian electricity sector with university-qualified education. Findings: Personal Ethics mitigates Emotional Exhaustion and Depersonalization, but it is not related to Personal Realization. Affective Commitment, unexpectedly, has an inverse moderating effect. In other words, as this type of commitment intensifies, the positive impact of Personal Ethics on Burnout and Depersonalization decreases until it disappears. Furthermore, Affective Commitment does not influence the dynamic between Personal Ethics and self-realization. Research limitations/implications: A longitudinal study would strengthen the causal relationships established in this research. Practical implications: Alignment of values between the individual and the organization is crucial. In fact, integration between the organization and its personnel through organic, open and connected structures increases psychological well-being through values linked to benevolence and understanding. Social implications: Employees’ emotional health is transcendental beyond the organizational level, as it has a significant impact on personal and family interactions beyond the workplace. Originality/value: The potential adverse repercussion of Affective Commitment has been barely examined. Additionally, Personal Ethics, when intensified by high Affective Commitment, can lead to extra-role behaviors that transform what is voluntary into a moral imperative. This situation could generate emotional fractures and a decrease in achievement. This perspective, compared to previous research, introduces an innovative element.